2020
DOI: 10.1088/1757-899x/912/6/062073
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Effect of Boric Acid on the Strength of High-Performance Concrete (HPC)

Abstract: Boron compounds are commonly used as a cementitious composite material for the attenuation of neutron and gamma radiation in HPC-M40. Boron compounds play a major role in the concrete for radiation shielding properties but addition of boric acid (H3BO3) to concrete drastically reduce hardening and strength. Commonly for radiation shielding of high thermal neutron boron based materials used in high purity concrete. In this study, different percentages of boric acid 1, 2, 3, 4 & 5% were added to the high-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is possible that the peak at 1184 cm −1 is caused by the out‐of‐plane bending vibrations of ‐B‐OH, while the peak at 1350 cm −1 is caused by the asymmetric stretching vibrations of ‐B‐O. The vibrations of the atoms in the B‐O bond are represented by the peak at 643 cm −1 , while the peak represents the bending vibrations of the O‐B‐O bond at 538 cm −1 80 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the peak at 1184 cm −1 is caused by the out‐of‐plane bending vibrations of ‐B‐OH, while the peak at 1350 cm −1 is caused by the asymmetric stretching vibrations of ‐B‐O. The vibrations of the atoms in the B‐O bond are represented by the peak at 643 cm −1 , while the peak represents the bending vibrations of the O‐B‐O bond at 538 cm −1 80 …”
Section: Resultsmentioning
confidence: 99%
“…The vibrations of the atoms in the B-O bond are represented by the peak at 643 cm À1 , while the peak represents the bending vibrations of the O-B-O bond at 538 cm À1 . 80 A comparative study of different chelating ligands for boron extraction from different matrices is shown in Table 9. The proposed flowsheet for boron extraction from a Sikait tourmaline ore sample from the Eastern Desert, Egypt, using PVC-MG-NMDG composite is presented in Figure 11.…”
Section: Dissolution Of Tourmaline Ore Samplementioning
confidence: 99%